Pelatihan Penerapan Media Digital Streaming Video Menggunakan Aplikasi Vmix pada UPTD BTIKP Disdik Sumsel - Rahman, M Arief; Aniswar, Irsanto; Permata, Rio; Hapsari, Yulia; Asoka, Egga; Sepriansyah, Ahmad Ari Gunawan; Ariyanti, Indri; Meranda; Apriana, Ina Opi; Pratiwi, Sindi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Training on the application of digital media streaming video using the vMix application at the UPTD BTIKP of the South Sumatra Disdik is a strategic step to meet the demands of the times in educational development. Involving employees, the training aims to improve their understanding and skills in implementing video streaming technology. Using a structured method, including an introduction, demonstration of the vMix application, individual practical sessions, discussions, and presentation of results, the training successfully provided participants with in-depth understanding and technical skills. The results include improved employee competencies in vMix implementation, creating the basis for a more innovative and technologically-adaptive education transformation.